ANALISIS PENGARUH SERVICE QUALITY TERHADAP CUSTOMER SATISFACTION BANK SYARIAH Studi Pada PT. Bank Muamalat Indonesia dan Bank Syariah Mandiri di Banjarmasin - Heldalina; Muhammad Riza Firdaus; Ikhwan Faisal (JWM (JURNAL WAWASAN MANAJEMEN), 2018)
The aim of this study was to: (1) analyze the influence of service quality variables (corporal efficiency, core banking, convenience, confidence, compliance and cost- benefit ratio) which simultaneously influence customers’ satisfaction of Bank Muamalat and BSM Banjarmasin branch, (2) analyze the influence of service quality variables (corporal efficiency, core banking, convenience, confidence, compliance and cost-benefit) which partially affect customers’ satisfaction of Bank Muamalat and BSM Banjarmasin branch, (3) analyze different levels of customers’ satisfaction (customer satisfaction) between Bank Muamalat Indonesia and Bank Syariah Mandiri (BSM). The population in this study were customers of Bank Muamalat Indonesia and Bank Syariah Mandiri Banjarmasin branch with a of 100 people. The technique used in taking sample was judgmental sampling. Testing the validity of the questionnaire was conducted using Pearson Product Moment, while the reliability test of questionnaire used Cronbach Alpha method. The data analysis was conducted using multiple linear regression and One-way ANOVA. Based on the results of multiple linear regression analysis it showed that the variables of service quality, that were, corporal efficiency, core banking, convenience, confidence, compliance and cost-benefit ratio simultaneously significantly affected customers’ satisfaction. Partially, only four variables that significantly affected, namely convenience, confidence, compliance and cost-benefit, while the corporal variable efficiency, core banking had no significant effect. Based on the analysis of one-way ANOVA it showed that there was no difference in satisfaction between customers of Bank Muamalat Indonesia and Bank Syariah Mandiri.